2020
DOI: 10.1093/cdn/nzaa097
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Epigenomics and Age-Related Disease

Abstract: Abstract Recent advances in epigenetic research have enabled the development of epigenetic clocks, which have greatly enhanced our ability to investigate molecular processes that contribute to aging and age-related disease. These biomarkers offer the potential to measure the effect of environmental exposures linked to dynamic changes in DNA methylation, including nutrients, as factors in age-related disease. They also offer a compelling insight into how imbalance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 123 publications
0
20
0
1
Order By: Relevance
“…The epigenetic clock and nutritional epigenomics may contribute to aging as well as age-related diseases [ 4 ]. Thus, mapping food-related chemical profiles (diet) and molecular pathways is the main goal of the network-based “Foodome” project ( https://www.barabasilab.com/projects ).…”
Section: Epigenetics and Risk Stratification Of Cvds: Network Medicinmentioning
confidence: 99%
“…The epigenetic clock and nutritional epigenomics may contribute to aging as well as age-related diseases [ 4 ]. Thus, mapping food-related chemical profiles (diet) and molecular pathways is the main goal of the network-based “Foodome” project ( https://www.barabasilab.com/projects ).…”
Section: Epigenetics and Risk Stratification Of Cvds: Network Medicinmentioning
confidence: 99%
“…A recent genome-wide DNA methylation study with 3096 participants demonstrated that tea and coffee consumption are also associated with altered methylation in two differentially methylated CpG sites (DNAJC16 and TTC17) [ 111 ]. Another study reported an association between ω-3 PUFA supplementation and vegetable and fruit consumption and lower GrimAgeAccel, DNAm PAI-1, DNAm ADM, and DNAm cystatin C which are considered epigenetic age markers enriched for DNA methylation sites that are surrogate biomarkers for blood plasma proteins related to aging [ 112 , 113 ].…”
Section: Effect Of Lifestyle and Environmental Factors On Epigenetic Modification In Older Adults With Cvdmentioning
confidence: 99%
“…Similarly, magnesium and selenium levels may function as potential epigenetic regulators via modulating different signaling pathways [ 112 , 113 , 122 ]. The possible epigenetic effects of selenium are the modulation of epigenetic information editors, interaction with miRNAs, as well as influence on the metabolism of a carbon, which acts as a methyl donor for DNA methylation [ 123 , 124 ].…”
Section: Effect Of Lifestyle and Environmental Factors On Epigenetic Modification In Older Adults With Cvdmentioning
confidence: 99%
“…These modifications are mediated by DNA methyltransferases (DNMTs) which transfer a methyl group from S-adenosylmethionine (SAM) to the acceptor nucleotide. The epigenetic clock theory of aging has been proposed by identifying DNA methylation signatures able to predict biological age and disease susceptibility [160].…”
Section: Nutrients As Epigenetic Modulators Of Health Span and Longevitymentioning
confidence: 99%